TOTAL QUALITY MANAGEMENT UNTUK PENDIDIKAN MENUJU N-GENERATION - Hastuti, Setyo (potensio, 2008)
Science develops fast nowadays. The unlimited informationmake someone able to create new things. But informationalso have negative effect, because it can make someoneget difficulty to make decisions. So, developing ofcreativities are needed in information era. This attitudes canbe found in n-agent, it is the attitude to choose suitable information, spread information in net working to create newideas. The ability to create new things from the existence ofthe information has to be developed in Educational System.So, the new generation will bore. The n-generation needsteacher’s corps that has high qualities and masters digitallanguage.Key Words: Education, N-Generation.